External validation of a pediatric decision rule for blunt abdominal trauma. Issue 1 (15th January 2022) - Sigal, Adam P.; Deaner, Traci; Woods, Sam; Mannarelli, Elizabeth; Muller, Alison L.; Martin, Anthony; Schoener, Alexis; Brower, McKenna; Ong, Adrian; Geng, Thomas; Guillen, Felipe; Lahmann, Brian; et al.
Abstract: Introduction: Blunt traumatic injuries are a leading cause of morbidity and mortality in the pediatric population. Contrast‐enhanced multidetector computed tomography is the best imaging tool for screening patients at risk of blunt abdominal injury. The Pediatric Emergency Care Applied Research Network (PECARN) abdominal rule was derived to identify patients at low risk for significant abdominal injury who do not require imaging. Methods: We conducted a retrospective review of pediatric patients with blunt trauma to validate the PECARN rule in a non‐pediatric specialized hospital from February 3, 2013, through December 31, 2019. We excluded those with penetrating or mild isolated head injury. The PECARN decision rule was retrospectively applied for the presence of a therapeutic intervention, defined as a laparotomy, angiographic embolization, blood transfusion, or administration of intravenous fluids for pancreatic or gastrointestinal injury. Sensitivity and specificity analysis were conducted along with the negative and positive predictive values. Results: A total of 794 patients were included in the final analysis; 23 patients met the primary outcome for an acute intervention. The PECARN clinical decision rule (CDR) had a sensitivity of 91.3%, a negative predictive value of 99.5, and a negative likelihood ration of 0.16. Conclusion: In a non‐pediatric specialty hospital, the PECARN blunt abdominal CDR performed with comparable sensitivity and negative predictive value to the derivation and external validation study performed at specialized children's hospitals.